Inter Moesos et Thraces : the rural hinterland of Novae in Lower Moesia (1st-6th centuries AD) - Tomas, Agnieszka, (Archaeopress Roman archaeology ;, 2016)
Excavations at the Roman legionary base at Novae in Lower Moesia reveal one of the most important sites in the Lower Danubian provinces. Towards late Antiquity, the military camp was transformed into a civil town with Episcopal residence and survived until the beginning of the 7th century.